Evaluation of an evidence‐based veterinary medicine exercise for instruction in clinical year of veterinary medicine program. Issue 1 (2nd April 2021) - Gibbons, Philippa M.; Anderson, Stacy L.; Robertson, Stanley; Thurman, Faythe K.; Hunt, Julie A.
Abstract: Introduction: Evidence‐based veterinary medicine (EBVM) is a fundamental core competency for new graduates. Our objectives were to evaluate clinical students' use, understanding of, and confidence in EBVM before undertaking an exercise consisting of an hour seminar in conjunction with a medical librarian, followed by a journal club and to evaluate students' knowledge of and ability to apply EBVM following the exercise. Methods: In this cohort study, students undertaking a large animal ambulatory rotation completed questionnaires before the seminar, following the journal club, and at graduation. Students took a Fresno test evaluating EBVM knowledge at the end of the rotation. Results: Prior to the seminar, 94% of students defined EBVM at least somewhat accurately, and 51% reported EBVM was at least 'quite important'. During previous rotations, 71% of students had performed literature searches to answer a clinician‐assigned question; 89% had done this to answer their own questions. Students with previous research or EBVM training were more likely to perform self‐directed literature searches. The most frequently used resource was textbooks. Eighty‐seven per cent and 90% of students found the seminar and journal club, respectively, at least moderately useful in improving EBVM knowledge. Conclusions: Our results support the inclusion of an EBVM exercise during the clinical year and suggest spaced repetition may be helpful in teaching this topic.